The case of the double cross - Bonsall, Crosby Newell, 1921- (New York : HarperTrophy, 1982)
Marigold concocts a mystery that finally gets her and her friends into the boys' private eye club.
"Grades 1-3"--Cover.
Bulletin (Center for Children's books).
School Library Journal.
2.4
K-3
Keywords: Ciphers -- Fiction; Clubs -- Fiction; Mystery and detective stories; Ciphers -- Fiction; Clubs -- Fiction; Mystery fiction; Mystery fiction; Readers (Elementary).